2023
DOI: 10.3389/fimmu.2023.1190394
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of complement serum C3 level and glomerular C3 deposits in anti-glomerular basement membrane disease

Abstract: Background and objectivesActivation of the complement system is involved in the pathogenesis of anti-glomerular basement membrane (anti-GBM) disease. Glomerular deposits of complement 3 (C3) are often detected on kidney biopsies. The primary objective of this study was to analyze the prognostic value of the serum C3 level and the presence of C3 glomerular deposits in patients with anti-GBM disease.MethodsWe conducted a retrospective cohort study of 150 single-positive patients with anti-GBM disease diagnosed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These levels were also inversely correlated with the SLE disease activity index and renal activity index scores [95]. Additional kidney diseases that show some evidence of complement activation include anti-GBM disease (Goodpasture's), diabetic nephropathy, and cryoglobulinemia [96][97][98][99].…”
Section: Complement and Kidney Diseasesmentioning
confidence: 92%
“…These levels were also inversely correlated with the SLE disease activity index and renal activity index scores [95]. Additional kidney diseases that show some evidence of complement activation include anti-GBM disease (Goodpasture's), diabetic nephropathy, and cryoglobulinemia [96][97][98][99].…”
Section: Complement and Kidney Diseasesmentioning
confidence: 92%
“…S7,S12–S14 A recent study by Caillard et al. 6 showed that C3 deposition in the glomeruli was associated with lower renal survival in initially nondialysis-dependent patients and, interestingly, much higher proportion of crescentic class; and underlines the importance of complement in anti-GBM disease, further pointing to the importance of histology. Moreover, a biopsy might reveal other findings; that is, periglomerular inflammation, granuloma or thrombotic microangiopathy, and anti-GBM disease can also occur with other primary and secondary glomerular diseases (antineutrophil cytoplasmic antibody-associated vasculitis, IgA nephropathy, membranous nephropathy, monoclonal gammopathy, etc.).…”
Section: Prognostic Factors–why a Kidney Biopsy Is Neededmentioning
confidence: 99%